2016
DOI: 10.1001/jamaoto.2016.0151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional, Revascularized, and Bioengineered Methods of Recurrent Laryngeal Nerve Reconstruction

Abstract: IMPORTANCE Damage to the recurrent laryngeal nerve (RLN) is highly detrimental to voice, swallow, and cough. The optimal method for reconstitution of a nerve gap after injury is unknown. OBJECTIVE To evaluate multiple methods of RLN reconstruction. DESIGN, SETTING, AND PARTICIPANTS This study used an established canine model of RLN injury to examine purpose-bred, conditioned, female, 20-kg mongrel hounds at Washington University. A total of 32 dogs were examined, with 63 experiments performed. INTERVENTIONS Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Pathophysiologically, a number of critical factors are involved in regeneration after nerve injury, including the activity of macrophages and Schwann cells, inflammatory reaction, and vascular regeneration. [7][8][9] In general, regenerating axons are only able to grow approximately 1 mm per day, [10][11][12][13] making regeneration across large nerve gaps particularly challenging. Autologous nerve grafting remains the gold standard treatment for treating nerve gap injuries; however, it has many shortcomings, such as the need for additional surgical procedures to retrieve a healthy functioning nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiologically, a number of critical factors are involved in regeneration after nerve injury, including the activity of macrophages and Schwann cells, inflammatory reaction, and vascular regeneration. [7][8][9] In general, regenerating axons are only able to grow approximately 1 mm per day, [10][11][12][13] making regeneration across large nerve gaps particularly challenging. Autologous nerve grafting remains the gold standard treatment for treating nerve gap injuries; however, it has many shortcomings, such as the need for additional surgical procedures to retrieve a healthy functioning nerve.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Las lesiones por neuropraxia pueden tomar de horas a meses para recuperarse, como ha sido reportado [1] , a diferencia de las lesiones segmentarias o tipo I, que usualmente obedecen a una sección del nervio o quemadura por difusión del calor secundaria al uso del electrocauterio, lo que hace muy poco probable su recuperación, aun cuando se haya hecho una neurorrafia. [19,20] Tomando en cuenta lo antes expuesto, el porcentaje de las pérdidas verdaderas de señal durante la cirugía tiroidea no es equiparable a la tasa de lesión recurrencial definitiva. Para poder establecerla con certeza, todos estos pacientes deberán ser reevaluados al cumplir un año de operados, para determinar el número exacto de nervios recurrentes laríngeos lesionados que provocaron una parálisis de cuerda vocal permanente o definitiva.…”
Section: Discussionunclassified
“…On the other hand, poor regeneration status at week 4 postsurgery and lightest muscle wet weight indicated that the NC used in this study had a negative effect in promoting nerve regeneration, which might be due to the inhibition of nutrient exchange. However, a limitation of the study is that it fails to preclude the possibility of using an NC, because different kinds of NCs present both positive and negative functions in different animal and clinical studies 24–27 . The conduit properties, including permeability, flexibility, physical inertness, and rate of degradation, are all important factors that can potentially impact the nerve regeneration result 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation of the study is that it fails to preclude the possibility of using an NC, because different kinds of NCs present both positive and negative functions in different animal and clinical studies. [24][25][26][27] The conduit properties, including permeability, flexibility, physical inertness, and rate of degradation, are all important factors that can potentially impact the nerve regeneration result. 28 Therefore, the effect of NC used in improving the outcome of semifascicle nerve grafts requires further investigation.…”
Section: Discussionmentioning
confidence: 99%